Practical materials characterization - Sardela, Mauro (Springer New York, 2014)
This unique book covers the most common materials analysis techniques, such as transmission electron microscopy, x-ray diffraction and reflectivity, auger electron spectroscopy, secondary ion mass spectrometry, photoelectron spectroscopy, and several optical characterization methods. It stands as a quick reference for experienced users, as a learning tool for students, and as a guide for the understanding of typical data interpretation for anyone looking at results from a range of analytical techniques. The book includes analytical methods covering microstructural, surface, morphological, and optical characterization of materials with emphasis on microscopic structural, electronic, biological, and mechanical properties. Many examples in this volume cover cutting-edge technologies such as nanomaterials and life sciences. This book also: ·         Presents cross-comparison between materials characterization techniques, including x-ray diffraction and reflectivity, x-ray photoelectron spectroscopy, secondary ion mass spectrometery, ellipsometry, Raman spectroscopy, and more ·         Includes clear specifications of strengths and limitations of each technique for specific materials characterization problem ·         Focuses on applications and clear data interpretation without extensive mathematics